2002
DOI: 10.1093/emboj/cdf583
|View full text |Cite
|
Sign up to set email alerts
|

Identification and reconstitution of theyeast mitochondrial transporter for thiamine pyrophosphate

Abstract: The genome of Saccharomyces cerevisiae contains 35 members of a family of transport proteins that, with a single exception, are found in the inner membranes of mitochondria. The transport functions of the 15 biochemically identified mitochondrial carriers are concerned with shuttling substrates, biosynthetic intermediates and cofactors across the inner membrane. Here the identification of the mitochondrial carrier for the essential cofactor thiamine pyrophosphate (ThPP) is described. The protein has been overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 43 publications
2
105
0
Order By: Relevance
“…Thus, net import of the substrate would occur, as predicted and shown experimentally for the transporters of thiamine pyrophosphate (Fig. S28 in SI Appendix) (39), oxaloacetate ( Fig. S11 in SI Appendix) (40), citrate (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, net import of the substrate would occur, as predicted and shown experimentally for the transporters of thiamine pyrophosphate (Fig. S28 in SI Appendix) (39), oxaloacetate ( Fig. S11 in SI Appendix) (40), citrate (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The recent discovery of the Tpc1p gene (5) in yeast (Swiss-Prot entry P53257, YGR096W) suggested another function for SLC25A19. Tpc1p transports ThPP produced in the cytosol into the mitochondria in exchange for mitochondrially generated ThMP, which then is metabolized and converted back to ThPP (5). In an in vitro exchange assay, we found that a protein containing the G177A mutation reduced ThPP and ThMP transport by Ϸ70% compared with wild-type protein.…”
Section: Discussionmentioning
confidence: 87%
“…While this study was underway, a novel mitochondrial transporter, Tpc1p, was discovered in Saccharomyces cerevisiae (5). This protein transports ThPP into the mitochondria in exchange for thiamine monophosphate (ThMP) and is the yeast protein most similar to human SLC25A19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHO3 represents a periplasmic acid phosphatase with a high affinity to thiamin phosphates and with an additional capability to tightly bind free thiamin [22]. A TPC1 gene encodes a mitochondrial membrane protein that transports TDP, synthesized de novo in the cytoplasm, into the mitochondria, where it can be incorporated into several essential TDP-dependent enzymes [23]. Our understanding of the genetic regulation of thiamin biosynthesis in yeast is at a very preliminary stage (for a recent review see: [3]), even though it has been known for four decades that the addition of thiamin to the medium represses thiamin synthesis and cellular uptake.…”
Section: The Genetic Control Of Thiamin Biosynthesis In Yeastsmentioning
confidence: 99%